Ethics of complementary medicine: practical issues - Ernst, Edzard (Royal College of General Practitioners, 2009)
Complementary medicine is popular, yet ethical issues are rarely discussed. Misleading information, informed consent, publishing, and confidentiality are discussed in the light of medical ethics. The message that emerges is that, in complementary medicine, ethical issues are neglected and violated on a daily basis.